Designing multilingual and multicultural curriculum - Alsu M. Gilmetdinova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
What is the relationship between language and culture? What role do language and culture play in designing curriculum that is inclusive of the needs of linguistically and culturally diverse students? What does multicultural and multilingual curriculum development look like? Scholarship on multicultural education acknowledges a strong interactive relationship between language, culture and learning and includes the benefits of bilingual instruction for multilingual students [10]; yet, often the assumption is that coming to voice takes place in English only [22]. Similarly, curriculum development for multicultural education is mainly done in the English language. The purpose of this article is to integrate both culture and language into the review of curriculum development that embraces both linguistic and cultural needs of diverse students. Using Sleeters [37] Un-Standardizing curriculum: Multicultural teaching in the standards-based classroom this targeted review encloses relevant scholarship in the fields of multilingual and multicultural education rooted in 4 central questions of curriculum theory: Question 1: What purposes should the curriculum serve? Question 2: How should knowledge be selected, who decides what knowledge is most worth teaching and learning, and what is the relationship between those in the classroom and the knowledge selection process? Question 3: What is the nature of students and the learning process, and how does it suggest organizing learning experiences and relationships? Question 4: How should curriculum be evaluated? How should learning be evaluated? To whom is curriculum evaluation accountable? [37] The results of the review provide educators and curriculum developers with much needed guidelines for developing comprehensive, culture and language sensitive curriculum.